Current Management and Future Challenges in the Management of Severe Traumatic Brain Injury - Larissa Russo; Aasim Kazmi; Nasim Ahmed (Medicina)
Background and Objectives: Severe Traumatic Brain Injury (TBI) is one of the devastating injuries occurring in all ages across the globe. Despite many advancements in the management of severe TBI, mortality and morbidities remain high. Evidence-based management in severe TBI has reduced mortality. The purpose of this review is to discuss the current management and present the future challenges in this patient cohort. Materials and Methods: A literature review was conducted to identify the current practice patterns and guidelines of severe TBI. We examined the literature regarding medical and surgical managements of the severe TBI. Results: Initial management of severe TBI includes stabilization of the primary injury and prevention of secondary insult to brain. Hemodynamic, intracranial pressure and cerebral perfusion pressure monitoring, antiseizure prophylaxis, hyperosmolar therapy, sedation, medical induced coma, and nutritional and ventilatory support are part of the medical management. Operative intervention includes craniotomy and decompressive craniectomy. Most of the current practices are recommended by the Brain Trauma Foundation (BTF). These guidelines are based on the existing literature, however, some of the recommendations by the BTF lack level one evidence. Conclusions: BTF guidelines provide recommendations in the management of severe TBI. High quality prospective randomized trials are needed to further explore the new modalities and interventions in the field of severe TBI.